Extracurricular language activities in higher education: Perspectives of teachers and students - Astafyeva, Evgeniya (fi=Turun yliopisto|en=University of Turku|, 2016)
This Master’s thesis researches the topic “Extracurricular language activities in higher education: Perspectives of teachers and students”. In the light of several learning theories, namely, Self-Determination Theory, Social Learning Theory and Incidental Learning Theory, extracurricular participation in language related activities is studied. The main aims of the research are as follows: to study how extracurricular language activities can be organized and supported by the education institution; to investigate how such activities can promote the participants’ learning; and, to research how these activities can be developed and improved in the future. Due to the qualitative character of this research, the empirical data collected through interviews and their thematic analysis allow to study the participants’ perceptions on the above-mentioned issues. Among other results of the research, it can be noted that the organizers of extracurricular language activities and the participants of the activities may have different perspectives on the aims of the activities, as well as their advantages. Additionally, it has been found that the participants of activities would often speak on certain categories that imply the connection to some learning theories, which allows to hypothesize that some learning could be observed in those participants, following participation in extracurricular activities. This is an implication for further research in the area, which can focus on correlations between participation in extracurricular language activities and learning outcomes of the participants.